2018
DOI: 10.1089/sur.2017.312
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Determinant Factors of Surgical Site Infection in Suhul Hospital Tigrai, Northern Ethiopia: A Cross-Sectional Study

Abstract: The magnitude of SSI was high. A hospital stay for more than a week, a history of alcohol consumption, use of local anesthesia, and dirty incision classification were associated independently with a higher risk of SSI. Due attention should be given to infection prevention control methods; and more has to be done to manage dirty and contaminated sites, maintain a strict sterile environment and aseptic surgical techniques, and implement the World Health Organization surgical safety protocol. Efforts should be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
9
17
1
Order By: Relevance
“…Patients with clean wounds were (99.4%) less likely to develop surgical site infection as compared to those patients with clean-contaminated wounds (AOR=0.006, 95% CI 0.002, 0.024). The finding was coherent with other researches done in Addis Ababa Ethiopia as the SSIs prevalence was higher in clean-contaminated wounds (50.0 %) than clean wound (15.7 %) (23), in Mekelle Ethiopia (29.5%) against (8.3%)(8), in Sudan (9.5%) versus (8%) (32) also in Bolivia (13.9%) compared to , (6.9%)(31). The low prevalence of SSIs on clean wounds in this study could be due to more precaution including antibiotic use for most clean wounds in the study setting.This study also identified, in open kept surgical sites, the odds of developing surgical site infection was 5.2 times as compared to close kept surgical site (AOR= 5.189, 95% CI 1.511, 17.821).…”
supporting
confidence: 90%
“…Patients with clean wounds were (99.4%) less likely to develop surgical site infection as compared to those patients with clean-contaminated wounds (AOR=0.006, 95% CI 0.002, 0.024). The finding was coherent with other researches done in Addis Ababa Ethiopia as the SSIs prevalence was higher in clean-contaminated wounds (50.0 %) than clean wound (15.7 %) (23), in Mekelle Ethiopia (29.5%) against (8.3%)(8), in Sudan (9.5%) versus (8%) (32) also in Bolivia (13.9%) compared to , (6.9%)(31). The low prevalence of SSIs on clean wounds in this study could be due to more precaution including antibiotic use for most clean wounds in the study setting.This study also identified, in open kept surgical sites, the odds of developing surgical site infection was 5.2 times as compared to close kept surgical site (AOR= 5.189, 95% CI 1.511, 17.821).…”
supporting
confidence: 90%
“…Contaminated surgical incision was found to be the risk factor for development of SSI. This finding is consistent with those reported in several previous studies performed in urology and general surgery wards (2,4,10,(15)(16)(17). Previous studies have reported correlation between wound class and development of SSI, the risk increases with classification of incision, surgeries on clean and cleancontaminated incision carry low risk compared to surgeries performed on contaminated and dirty incisions, which might be accounted for by high loading dose of microbes (7,18,19).…”
Section: Discussionsupporting
confidence: 93%
“…Infection prevention, particularly in surgical wards, could not be ignored since the infection is critical and easily spreads throughout the hospital making the surgical wards a focal point [29]. e history of surgical intervention, the nature of surgical interventions, longer duration of surgical procedures, and the overcrowding of bed in wards may contribute to the variation [18,20]. e observed discrepancy may also be due to the differences in sample size, methods adopted, and inclusion criteria.…”
Section: Advances In Preventive Medicinementioning
confidence: 99%
“…e existing literatures, particularly in sub-Saharan Africa countries, were restricted to certain wards of the hospitals [17][18][19]. Likewise, studies conducted in Ethiopia are mainly limited to particular sites of infections [20][21][22], but minimizing HCAIs within the hospitals is a key aspect of patient safety initiatives.…”
Section: Introductionmentioning
confidence: 99%